Peranan Badan Kepegawaian Daerah Dalam Pelaksanaan Mutasi Pegawai Negeri Sipil Di Kabupaten Kepulauan Talaud - Taengetan, Kritino Rizky; Laloma, Alden; Ruru, Joorie (Sam Ratulangi University, 2015)
ABSTRACT :This research is to know the role of the Agency in the implementation of regionalstaffing mutation civil servant in talaud Islands Regency. Talaud Islands Regency Area Staffing Agencyhas an important role in improving the performance of civil servants and is responsible for theimplementation of mutation and mutational effects on the welfare of civil servants. One example is not aseffective as the role of the Agency in the implementation of Regional Staffing i.e., mutation mutation civilservant in the Regency Talaud rated still tend to have political interests as a cornerstone of itsimplementation which we know as the seniority system and spoil system we know together not because ofhis objective based on seniority and family. So the performance of the Agency's Staffing Area in particularin the implementation of the mutation is still not qualified because its implementation is not based on theground of a mutation that we are familiar with the term meryt system or mutations that uses up therunway that is scientific, objective, and outcomes achievement it works.This research uses Qualitative Research Methods by using techniques of data analysis throughinterviews to 10 Informants, observation and document additional instrument-assisted search formguidelines interview with using techniques of data analysis, data presentation, data reduction, andwithdrawal of the conclusion.Based on the research results through data analysis, and performance measurement indicators.The following is the measurement indicators: productivity (effectiveness and efficiency), quality of service,Responsiveness, Accountability, corporate responsibility. Talaud Islands Regency BKD in itsimplementation is still not good, let alone in carrying out duties, functions, and his authority insurveillance, designation, the rules of the mutation. the performance of human resources Staffing Agencyin Areas still not in optimize thoroughly. It was evident from the coordination between subordinates andsuperiors are still unfavourable, liability is still very closed, in addition to Staffing The Agency also doesnot answer the needs of society in General.Referring to the conclusions above, shall recommend in a good cooperation between, civilservants, with Staffing Agencies, Staffing Agencies and Regional Areas and local governments mustfacilitate the work of civil servants by holding trainings – training.Key words: the role of the Agency in the implementation of regional staffing mutations.